Comparison of the lived experiences of family caregivers of patients with dementia and of patients with cancer in Indonesia. (5th September 2017) - Kristanti, Martina Sinta; Engels, Yvonne; Effendy, Christantie; Astuti,; Utarini, Adi; Vernooij-Dassen, Myrra
ABSTRACT: Background: Dementia, even more than cancer, demands long-term care. While in Indonesia cancer is accepted as a disease requiring caregiving, dementia is still considered "a normal condition." These differences might affect the experiences of caregivers, especially those relating to social health, the subject of our study. We aim to describe and compare the lived experiences of family caregivers of patients with cancer (PWC) with those of patients with dementia (PWD) in Yogyakarta, Indonesia, and to explore the role of their social health in these experiences. Method: A qualitative design was applied. In-depth face-to-face interviews were conducted with PWC and PWD caregivers in two outpatient clinics of a tertiary hospital. The constant comparative method was applied to analyze the data that were interpreted using the concept of social health to explore the experiences of the caregivers. We used Atlas.ti software. Results: Three themes were identified: problems with caregiving, dealing with problems, and beliefs in caregiving. We found more similarities than differences in the experiences of caregivers in both groups. Half of the categories were related to social health: challenges, consequences, hiding, social support, and the caregiver's approach. The organization of dementia care is characterized by simplicity and direct ties between medical specialists, PWD, and caregivers, whereas cancer care encounters coordination problems. Conclusions: Family caregivers of both groups mostly had similar experiences of the caregiving process. Gaining a better understanding of the specific experiences of caregivers, and their social health, opens new avenues for interventions to improve their quality of life.